DETERMINATION OF PARAMETER QUALITY OF GROUND WELL WATER USING ADSORBENT FILTER FROM RICE HUSK ASH - Said, Yahya; -, Alimuddin; Gunawan, Rahmat (JURNAL ATOMIK, 2021)
Determining the parameters of the quality of well water in Mugirejo, Sungai Pinang, Samarinda, using an adsorption filter from rice husk ash, has been carried out. Determination of the optimum flow rate and the level of each water quality parameter BOD, TSS and levels of metals (Pb, Fe, Mn). Based on the results of the filtration process in well water samples showed that the effect of the flow rate obtained the optimum flow rate of 1 hour per liter against decreasing levels of BOD, TSS and levels of metals (Pb, Fe and Mn) of 8.1, 17.28 mg/L O2, 1.4 mg/L, 68 mg/L, ND (No Detection), 0.0012 µg/mL and 0 µg/mL. For the flow rate of ½ hour per liter against decreases in BOD, TSS and levels of metals (Pb, Fe and Mn) respectively at 8.0, 30.52 mg/L O2, 2.01 mg/L, 46 mg/L, 0 µg/mL, 0.0109 µg/mL and 0.021 µg/mL.